Peningkatan Kompetensi dalam Menyusun dan Mengembangkan Buku Teks bagi Guru-guru di MAN 1 Lombok Barat - Ihsani, Baiq Yuliatin; Lamusiah, Siti; Darmurtika, Linda Ayu; Akhmad, Akhmad (Lembaga Yasin AlSys, 2023)
This community service activity was carried out with the aim that teachers are able to compile and develop textbooks. This PKM program was held at MAN 1 West Lombok. This PKM program was carried out for 3 (three) days. The method of implementing activities used in the community service program is training (coaching) accompanied by mentoring. This PKM program was carried out by 3 lecturers and assisted by 3 students. Based on the results of the implementation of activities, it can be described that after the service is carried out, the ability of teachers to compile and develop textbooks has increased. This can be seen from the teacher's test results before and after the activity. Before the training, out of 30 training participants, 15 people were able to answer correctly and the rest answered incorrectly or in other words before the activity was carried out the percentage of teacher ability was only 50%, after the PKM activity, the teacher's ability increased to 100%. In addition, the ability of teachers to develop textbooks has been seen from the results of the teacher's work through the assistance of lecturers implementing activities.